Academy of Management News (Academy of Management Journal, 1964)
The article offers news briefs related to the Academy of Management as of December 1964. The Academy of Management Research Committee has announced its program of management research grants for 1965 to be undertaken with the cooperation and support of the American Management Association. The Ralph Currier Davis Management Symposium was held at Ohio State University on November 12 and 13 to honor Dr. Ralph C. Davis who expects to retire from Ohio State’s business organization faculty in 1965. Plans are moving ahead for the Spring meeting of the Eastern Division of the Academy of Management to be held at the Wharton School of the University of Pennsylvania.